2016
DOI: 10.4028/www.scientific.net/kem.702.91
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Optical Properties in Sn, Sb, Pb and Bi Doped Silica Glasses Aiming Visible Fiber Laser

Abstract: Emission spectra of Sn, Sb, Pb and Bi doped silica glasses co-doped with Al and P prepared by modified chemical vapor-phase deposition (MCVD) using solution doping technique are presented. Bi doped silica glasses present emission/excitation (Em/Ex) bands around 470/(330, 220nm) 600/(470, 350, 270nm), 730 and 830/(820, 420, 380, 250nm), with the intensity ratio of these bands depends on the composition, indicating that different emission sources (valence states or defects) are present together. The Em/Ex of Sb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…[55] Under 800 nm excitation, a broadband NIR emission with a peak at 1260 nm and a lifetime of ≈ 40 μs was observed (Figure 11). They suggested that the NIR emission [88] Copyright 2016, Trans Tech Publications Ltd.…”
Section: Sb-doped Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…[55] Under 800 nm excitation, a broadband NIR emission with a peak at 1260 nm and a lifetime of ≈ 40 μs was observed (Figure 11). They suggested that the NIR emission [88] Copyright 2016, Trans Tech Publications Ltd.…”
Section: Sb-doped Materialsmentioning
confidence: 99%
“…[87] In 2016, Sekiya et al prepared Sb-doped low-P silica glass by MCVD method. [88] In addition, a Bi-doped sample was prepared under the same conditions in order to compare the difference in luminescence. As shown in Figure 16, Sb-containing samples exhibit two emission bands with peaks at 830 and 1400 nm under multiple wavelength excitation.…”
Section: Sb-doped Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Висмутсодержащие силикатные стекла представляют интерес в связи с тем, что обладают люминесценцией в широком спектральном диапазоне от ближней УФ области до ближней ИК области, включая диапазон 1150−1800 nm, благодаря присутствию различных висмутовых активных центров (ВАЦ) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Известны различные способы получения висмутсодержащих стеклообразных оптических материалов силикатных, алюмосиликатных, фосфатно-силикатных систем с люминесцентными свойствами.…”
Section: Introductionunclassified
“…Известны различные способы получения висмутсодержащих стеклообразных оптических материалов силикатных, алюмосиликатных, фосфатно-силикатных систем с люминесцентными свойствами. К таким способам получения относятся метод закалки расплава (варка из шихты, conventional melting-quenching technique) [2,3,13,14,18], порошковая технология (powder-in-tube) [10, 12,17], метод осаждения из газовой фазы (методы модифицированного химического парофазного осаждения, Modified Chemical Vapor Deposition -MCVD) [10, 11,17]. Указанные способы получения висмутсодержащих стекол предполагают проведение синтеза в условиях высокой температуры ∼ 1050−2200 • С [2,3,[10][11][12][13][14]17], что не позволяет регулировать степень окисления висмута и, следовательно, природу ВАЦ и характер люминесценции.…”
Section: Introductionunclassified